Acoustic Emission Characteristics of Fault Activation under the Influence of Coal Roadway Driving - Pengbo Wang; Jie Hu; Guichun Lv; Jingyuan Guo; Qiao Xiao (Shock and Vibration)
To investigate the impact of coal roadway excavation on the fault activity, this study examined the acoustic emission (AE) count, energy characteristics, and evolution of the AE b-value during the tunneling process across a fault by utilizing field data from the KSA outburst early warning system and applying the Gutenberg–Richter (G-R) law. The results showed the following. In terms of the time span, the AE count and energy showed trends of first increasing and then decreasing during the excavation of a coal roadway through a fault. AE events as the driving face passed through the fault conformed to the G-R law. A lower b-value corresponded to a higher frequency of high-energy events, indicating a more pronounced disturbance of the driving face on the fault. There was a continuous increase in the energy release from the fault and an escalating level of hazard associated with the driving face. The variation of the b-value during the passage of the driving face across the fault could be delineated into three distinct stages, namely, a fluctuation stage, a decline stage, and a recovery stage. In the fluctuation stage, the driving work exerted minimal influence on the fault behavior. The decline stage represented the most active phase for fault activity, with a heightened risk to the driving face. Finally, in the recovery stage, as the distance between the driving face and the fault increased, there was a gradual reduction in the impact of the fault activity on the working face operations.